Ballistic resistant laminate. - Ali, Aidy; Abdan, Khalina; Shaker Radif, Zainab (2010)

(untitled)
The present invention discloses a ballistic laminate structure comprising a plurality of layers of ballistic cloth and a plurality of layers of natural fibre, one or more of which layers is treated with an adhesive material. In carrying out the invention, there is provided a multi-ply ballistic fabric comprising a plurality of plies woven of aramid fibres, such as Kevlar and a multi-ply woven fibre derived from ramie plant. One or more of the ply of aramid fibres and/or woven fibre derived from ramie is impregnated with a thermosetting resin.